The formation of the atrioventricular conduction axis is linked in development to ventricular septation - Kvasilova, Alena; Olejnickova, Veronika; Jensen, Bjarke; Christoffels, Vincent M; Kolesova, Hana; Sedmera, David; Gregorovicova, Martina (The Journal of experimental biology, 2020)
During development, the ventricles of mammals and birds acquire a specialized pattern of electrical activation with the formation of the atrioventricular conduction system (AVCS), which coincides with the completion of ventricular septation. We investigated whether AVCS formation coincides with ventricular septation in developing Siamese crocodiles (Crocodylus siamensis). Comparisons were made with Amazon toadhead turtle (Mesoclemmys heliostemma) with a partial septum only and no AVCS (negative control) and with chicken (Gallus gallus) (septum and AVCS, positive control). Optical mapping of the electrical impulse in the crocodile and chicken showed a similar developmental specialization that coincided with full ventricular septation, whereas in the turtle the ventricular activation remained primitive. Co-localization of neural marker human natural killer-1 (HNK-1) and cardiomyocyte marker anti-myosin heavy chain (MF20) identified the AVCS on top of the ventricular septum in the crocodile and chicken only. AVCS formation is correlated with ventricular septation in both evolution and development.
Keywords: Heart; mezikomorová přepážka; převodní systém srdeční; Animals; Embryo; Alligators and Crocodiles; kardiomyocyty; Chicken; zvířata; Ventricular Septum; srdeční komory; Turtle; Heart Conduction System; Myocytes, Cardiac; Heart Ventricles; Crocodile; aligátoři a krokodýli